1991
DOI: 10.1007/bf00167901
|View full text |Cite
|
Sign up to set email alerts
|

Continuous production ofl-lactic acid from whey permeate by immobilizedLactobacillus casei subsp.casei

Abstract: The production of L-lactic acid from whey permeate, a waste product of the dairy industry, by fermentation with the lactic acid bacterium L a c t o b a c i l l u s casei subsp, casei was investigated. A fermentation medium consisting of permeate and supplements, which enables exponential growth of the organisms, was developed. A fast method for determination of free and immobilized biomass in solid-rich media, based on measurement of cellular ATP, was evolved. Continuous fermentations in a stirred tank reactor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
50
1
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(58 citation statements)
references
References 12 publications
4
50
1
1
Order By: Relevance
“…However, at higher and lower pH levels, a decrease in the both the function was observed, with significant decrease at pH 6.0 and 7.0. A pH range of 6.0-6.5 has been reported optimal for lactic acid production using L. casei strain (Krischke et al, 1991). However, pH 5.5 has been used for lactic acid production using L. helveticus by (Ghaly et al, 2004).…”
Section: Effect Of Phmentioning
confidence: 99%
See 1 more Smart Citation
“…However, at higher and lower pH levels, a decrease in the both the function was observed, with significant decrease at pH 6.0 and 7.0. A pH range of 6.0-6.5 has been reported optimal for lactic acid production using L. casei strain (Krischke et al, 1991). However, pH 5.5 has been used for lactic acid production using L. helveticus by (Ghaly et al, 2004).…”
Section: Effect Of Phmentioning
confidence: 99%
“…L. helveticus, and L.acidophilus can be used in a temperature range of 37-45°C. Krischke et al, (1991) used 37°C temperature for lactic acid production using L. casei. However, a temperature of 28°C has also been reported optimal for L. casei in a separate study (Nabi et al, 2004).…”
Section: Effect Of Temperaturementioning
confidence: 99%
“…Krischke et al 10 found that best growth and product formation occurred between pH 6.0 and 6.5 for immobilized L casei subsp casei grown on whey permeate. key factors in lactic acid fermentation.…”
Section: Effect Of Phmentioning
confidence: 99%
“…For batch fermentation of whey permeate by L casei subsp casei, Krischke et al 10 concluded that the best growth comparable to MRS medium occurred with a combination of yeast extract (5 g dm −3 ) and hydrolyzed whey retentate (50 g dm −3 ). Guoqiang et al 12 determined that increasing yeast extract concentration (0-10 g dm −3 ) increased lactic acid production.…”
Section: Effect Of Yeast Extractmentioning
confidence: 99%
See 1 more Smart Citation